SOLUTION
We want to factor
![x^3-64=0](https://img.qammunity.org/2023/formulas/mathematics/college/l9ai1pyfu8x7rbrfeof2mujlz00ytkar8y.png)
Looking at this, we can tell that (x - 4) or (x + 4) would be one of its factors, since 4 is a factor of 64. So let use check for (x - 4)
So, we will put x = 4 into the equation, we have
![\begin{gathered} x^3-64 \\ 4^3-64 \\ 64-64=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lad5yvqcgms9faqi1oiw6l0wyoss79no1u.png)
hence (x - 4) is a factor. Dividing the polynomial by (x - 4), we have
![(x^3-64)/(x-4)](https://img.qammunity.org/2023/formulas/mathematics/college/bxz27g9g3wnoi9qv51rkhk5ar7ozrade8r.png)
so we got
![x^2+4x+16](https://img.qammunity.org/2023/formulas/mathematics/college/mrjabpyx5ujsouq92ouvqjombgtafkol51.png)
Factorizing the result, we have
![\begin{gathered} x^2+4x+16 \\ We\text{ find the discriminant using } \\ D=b^2-4ac \\ D=4^2-4*1*16 \\ D=16-64 \\ D=-48 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6l4amtmr5ns6sw9afc74bpponpugkpb1ib.png)
Now we have the discriminant, we use the formula to fin the roots of this equation, we have
![\begin{gathered} x_1=(-b-√(D))/(2a) \\ =(-4-√(-48))/(2*1) \\ =(-4-4√(3)i)/(2) \\ =-2-2√(3)i \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/e4ww575yxx5scxep7k7ynin86n4rq6zee1.png)
The second root becomes
![\begin{gathered} x_1=(-b+√(D))/(2a) \\ =(-4+√(-48))/(2*1) \\ =(-4+4√(3)i)/(2) \\ =-2+2√(3)i \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hbqfvcsopwwdznvjlo2eozr5loj3zvpur1.png)
Note that square root of -1 is i
So, comparing to the options, we can see that
The answer is option D